2005
DOI: 10.1128/cdli.12.5.654-659.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Persistence of Chlamydia pneumoniae Antibodies in Healthy Laboratory Personnel in Finland

Abstract: The rates of Chlamydia pneumoniae seroconversions suggesting acute primary infections or reinfections and the prevalences of antibodies were followed up among healthy laboratory workers. Annual serum samples were collected from 47 persons in Helsinki from 1958 to 1990 and from 40 persons in Oulu from 1994 to 1999. C. pneumoniae species-specific immunoglobulin G (IgG), IgA, and IgM antibodies were measured by microimmunofluorescence (MIF) in 407 sera from Helsinki. The 185 sera collected in Oulu were tested bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
4
18
1
Order By: Relevance
“…Previously it has been reported that increased IgA antibody levels reflects an active or persistent infection, whereas IgG levels reflect only a previous or past infection with C pneumoniae [26]. Our data also suggest that those CAD patients having IgA antibodies in their serum indicate a persistent or active infection while patients having both IgA and IgG may reveal chronicity of persistent active infection and the presence of IgG alone reflects past infection.…”
Section: Discussionsupporting
confidence: 70%
“…Previously it has been reported that increased IgA antibody levels reflects an active or persistent infection, whereas IgG levels reflect only a previous or past infection with C pneumoniae [26]. Our data also suggest that those CAD patients having IgA antibodies in their serum indicate a persistent or active infection while patients having both IgA and IgG may reveal chronicity of persistent active infection and the presence of IgG alone reflects past infection.…”
Section: Discussionsupporting
confidence: 70%
“…In our mouse model, the 2-month periods between the 3 inoculations allowed the mice to recover fully from the clinical signs of the disease; they therefore simulate the possible re-infection frequency in people, since epidemics generally occur every 4-6 years Vol. 57, 2008 C. pneumoniae re-infections in a mouse model 293 [23]. The relatively low inoculation dose of C. pneumoniae might be closer to those in natural human infections than the much higher doses used for inoculation in some other studies [16,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…IgG antibody can persist long after the acute phase (Puolakkainen et al, 1986; Paldanius et al, 2005), and only reflects (previous) exposure to the organisms. Some markers have yet been brought forward.…”
Section: Serologymentioning
confidence: 99%